Implémentation d’un proto de réhabilitation fonctionnelle en A P A chez les personnes atteintes de lombalgie. - ZENATI, Yassine (l’Université de Mostaganem, 2021)
Research objectives: To evaluate a functional rehabilitation protocol for people with low back pain.We have adopted the use of the experimental method, in order to answer the questions related to our research, on a sample of nine people,chosen deliberately by the specialist doctor, Their age varies between 41 and 53 years, are subject to the protocol which lasted 15 weeks,and for data collection, a follow-up is carried out: at each consultation, the interview and the clinical examination state the absence of warning signs. the following tests were carried out: Questioning; Pain assessment (EVS scale); Evaluation of the functional impact of low back pain (EIFEL scale); Spine mobility assessment: Measurement of the mobility of the thoraco-lumbar spine in flexion, The mobility of the dorso-lumbarspine in extension, Evaluation of the tilting motion of the spine; and endurance of the abdominal and Lumbar Spinal Muscles. After collecting the data and processing it statistically, we came to a set of conclusions:The implementedprotocolcontributed to reduce pain (the degree of pain has diminished); an improvement in functional capacities to carry out activities in daily life, so it brought changes that would allow people with low back pain to learn to manage this pain. The protocol implemented has a positive effect on the improvement of certain variables: Contributed to the improvement of the mobility of the dorso-lumbarspine in extension; Contributed to the improvement of the tilting movement of the spine to the right and to the left; and contributedto improving muscle endurance abdominals and lumbarspines.On this basis, the studyrecommended :Developed a treatmentpathtranslated by the protocolvalidated in ourstudy,by creatingagreements of several care providersto materializethe protocolrelating to people withcommonlow back pain. .
Keywords: functionalrehabilitationprotocol, adapted physical activity, commonlow back pain